Pengaruh Top Brand Image BSI Terhadap Keputusan Mahasiswa Memilih Akademi BSI - Endang Retnoningsih - AMIK BSI Tangerang (Evolusi : Jurnal Sains dan Manajemen, 2015)
Abstract   Brand image which has recognition as a top brand image is one asset and one of the important considerations for students before determining the choice of college. Background research on the influence of top brand image on the decision of the Academy students in choosing BSI has get Top Brand Award for two years  in 2013 and 2014. The research purposes to prove the hypothesis of research there is a positive correlation between top brand image with the decision of students choosing BSI Academy. To find out how much influence BSI’s top brand image on the decision of students chose the Academy of BSI, used statistical analysis is based on data obtained through questionnaires measured using Spearman Rank correlation and coefficient of determination. Based on the research that the respondents to BSI’s top brand image is a good, which is indicated by a value of 3.70. And from the findings that the decision of the respondents chose the Academy BSI is good, which is indicated by a value of 3.44.Results of Spearman Rank correlation coefficient is rs = 1.000, indicating that there is a strong and direct relationship between these two variables, the results of the calculation of determination coefficient of 100%, meaning if BSI’s top brand image both the number of students who choose academy BSI will be increase.   Keywords : Brand Image, Top Brand, Students Decision.